METAMETAPHORISM IN THE RUSSIAN ART OF THE 1970S AND 1980S (Philological Studies, 2019)
The article discusses metametaphorism in poetry and painting of the 1970s and 1980s, explains similar trends in the works of Russian poets and artists. Metametaphorism in poetry has gained its popularity due to the ideology of the Konstantin Kedrov`s poetic school represented by Ivan Zhdanov, Alexei Parshchikov, Alexander Eremenko. In their poems principle of the eversion constructs the poetics of the text, as well as on the phonetic level - the principle of anagramma. Special attention is drawn to the plot of the creation of the world. The same interest to the emergence, disappearance, transformation, but not a thing in its outlines one can find in the paintings of Nicholay Zarubin, which refers to the technique of bleed-through figures.
Keywords: metametaphorism, metametaphora, metaphor, eversion, anagramma, zoom-effect, the technique of bleed-through figures